Chemical composition and industrial applications of maritime pine (Pinus pinaster Ait.) bark and other non-wood parts - Alonso-Esteban, José Ignacio (2022)
Maritime pine (Pinus pinaster Ait.) is native to the western Mediterranean basin and has an economic importance in southwestern Europe. This importance is based on the use of its wood in the construction, furniture, and paper industries. Bark and other parts of the plant, such as resin, needles, and cones, are by-products with potential industrial application. These parts of the tree stand out because of the presence of secondary metabolites, the main ones being phenolic compounds and terpenes. Bark contains both, while other parts of the plant are mainly composed of terpenes. All these compounds have biological potential, mainly antioxidant and antimicrobial properties. The bark has the widest range of industrial applications, and it can be used to obtain dietary supplements and functional foods, adsorbents, and bio-based resins and foams. Resin has a prominent industrial role too, especially in chemical industry. In this manuscript, an overview of these applications is described, opening an innovation opportunity for enterprises to use the by-products and residue of maritime pine. Still, albeit the described application, maritime pine has further applications that are right now being studied under the premises of circular economy.